2012
DOI: 10.2139/ssrn.1981983
|View full text |Cite
|
Sign up to set email alerts
|

Lag Length Selection for Unit Root Tests in the Presence of Nonstationary Volatility

Abstract: A number of recently published papers have focused on the problem of testing for a unit root in the case where the driving shocks may be unconditionally heteroskedastic. These papers have, however, assumed that the lag length in the unit root test regression is a deterministic function of the sample size, rather than data-determined, the latter being standard empirical practice. In this paper we investigate the finite sample impact of unconditional heteroskedasticity on conventional data-dependent methods of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
(18 reference statements)
0
13
0
1
Order By: Relevance
“…By using the first difference data, we find that the number of lags is same as 1 for all three different criterions. According to Tsay (1984), Potscher (1989), and Cavaliere et al (2015), BIC is consistent compared to AIC because AIC overestimates with positive probability. Therefore, we use BIC information.…”
Section: Df-gls Unit Root Testmentioning
confidence: 96%
“…By using the first difference data, we find that the number of lags is same as 1 for all three different criterions. According to Tsay (1984), Potscher (1989), and Cavaliere et al (2015), BIC is consistent compared to AIC because AIC overestimates with positive probability. Therefore, we use BIC information.…”
Section: Df-gls Unit Root Testmentioning
confidence: 96%
“…While the choice of lag selection criteria may not necessarily affect asymptotic properties of unit root tests, it might however impact on finite sample performances of tests in the presence of heteroskedasticity. Cavaliere et al () have shown that standard lag selection criteria tend to over‐fit the lag order in the presence of heteroskedasticity and, hence, induce power losses in the (wild bootstrap version of the) univariate augmented Dickey–Fuller tests. Their modified lag selection criteria, which rescale the data by an estimate of the underlying time‐varying volatility process, significantly mitigate the power losses while retaining comparative size properties.…”
Section: Homogeneous Panel Unit Root Testingmentioning
confidence: 99%
“…Denoting this estimated lag length byp, we also then set p * =p in Step 4 of Algorithm 1 for all of the simulation results we report here. To obtain our estimatep we propose a seasonal generalisation of the heteroskedasticity-robust re-scaled modified information criterion [MIC] based method of Cavaliere et al (2015), designed to account for non-stationary volatility in the shocks by using re-scaled data. Our suggested approach consists of applying their re-scaling approach to each of the seasons separately.…”
Section: Finite Sample Simulationsmentioning
confidence: 99%
“…Monte Carlo simulations for a variety of (periodic) non-constant volatility models suggest that the wild bootstrap HEGY tests perform very well in practice with only small finite sample differences between the two wild bootstrap schemes. We also outline how the re-scaled information-based lag length selection methods of Cavaliere et al (2015) can be adapted to the seasonal unit root testing case.…”
Section: Introductionmentioning
confidence: 99%